Carbohydrates-A Brief Deliberation with Bio-aspect - Khadka, Yagya Rath (Cognition, 2022)
Carbohydrate is an organic molecule having carbon, hydrogen and oxygen as chief elements. It is mostly sugary in taste and categorized in three different types according to the presence of carbon numbers in the molecule. It bears two different functional groups i.e. aldehyde (-CHO) and ketone (>CO) with different spatial configuration, resulting different isomers. Amongst many of the roles, one of the most important is the formation of structural formation of RNA and DNA. Metabolic activities like glycolysis (pathway to convert glucose to pyruvate), citric acid cycle (final oxidative pathway for carbohydrate, fats and amino acids), gluconeogenesis (synthesis of glucose from non-carbohydrate precursors), glycogenesis (synthesis of glycogen from glucose in presence of ATP) and glycogenolysis (degradation of stored glycogen) are the major functions. Carbohydrate undergoes various mechanism by which necessary product are formed, as a result human body easily function and synthesize many compounds within the human body. Obesity, diabetes mellitus, hypoglycemia are some disease condition arose due to high level of carbohydrate concentration in the body.